2014
DOI: 10.1074/jbc.m114.569061
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plasma Kallikrein by a Highly Specific Active Site Blocking Antibody

Abstract: Background: Unregulated plasma kallikrein proteolytic activity can result from C1-inhibitor deficiency, causing excessive and potentially fatal edema.Results: The antibody DX-2930 potently and specifically inhibits plasma kallikrein and exhibits a long plasma half-life.Conclusion: An antibody protease inhibitor can lead to potent and specific bioactivity.Significance: DX-2930 could be an effective therapeutic for the prophylactic inhibition of plasma kallikrein-mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
110
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 74 publications
0
110
2
Order By: Relevance
“…Moreover, the P1 Arg residue forms a suboptimal interaction in which a water molecule is required to mediate the interaction between the P1 Arg residue and Asp-189 at the bottom of the S1 pocket. In contrast, the anti-plasma kallikrein antibody DX-2930 binds in the normal N-to C-terminal orientation, but a non-substrate-like conformation of the loop prevents it from binding the S1Ј-S3Ј pockets and thereby hydrolysis of the putative scissile bond (21). The anti-HGFA Fab58 also binds to the active site region of the protease, occluding the S2 and S3 but not the S1 pocket (20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the P1 Arg residue forms a suboptimal interaction in which a water molecule is required to mediate the interaction between the P1 Arg residue and Asp-189 at the bottom of the S1 pocket. In contrast, the anti-plasma kallikrein antibody DX-2930 binds in the normal N-to C-terminal orientation, but a non-substrate-like conformation of the loop prevents it from binding the S1Ј-S3Ј pockets and thereby hydrolysis of the putative scissile bond (21). The anti-HGFA Fab58 also binds to the active site region of the protease, occluding the S2 and S3 but not the S1 pocket (20).…”
Section: Discussionmentioning
confidence: 99%
“…1).415 To complicate matters further, our own experience shows that 416 the randomness in the distribution of residuals, when considered 417 in isolation, is not a suitable measure of significant nonlinearity 418 in enzyme kinetics. If fact, we found that in certain exquisitely419 well-tuned enzyme assays[19], the random scatter in the data 420 points is so low that even insignificant departures from linearity 421 (e.g., those observed at extremely low final substrate conversions)422 will produce decidedly nonrandom residual patterns.423 Based on similar practical reasons, we hereby propose an oper-424 ational definition of nonlinearity in the context of covalent enzyme425 inhibition kinetics, which is inspired by the ''cross-validation'' con-426 cept from statistics[16]. The basic idea is to divide the control pro-427 gress curve into two halves, fit each segment to the straight line 428 model, and finally compare the two resulting slopes, that is, the 429 ''initial'' and ''final'' reaction rates.…”
mentioning
confidence: 97%
“…A second phase is mediated by bradykinin. An antibody blocking PKal, an enzyme that cleaves high molecular weight kininogen to generate bradykinin, produced significant inhibition of edema in this model [249].…”
Section: Surrogate Non-ocular Modelsmentioning
confidence: 99%